Glossing and incidental vocabulary learning in L2 reading: a cognitive load perspective - Unal, Burcu (WALTER DE GRUYTER GMBH, 2023)
Considering the relationship between reading and incidental vocabulary learning, in this study the effects of electronic glosses as well as working memory (WM) capacity on readers' intake of new words were investigated. One hundred twenty users of English read an electronic text annotated with either lexical or topic-level glosses placed in either a pop-up window or a separate window. Upon reading, they took immediate and delayed form recognition and meaning recall tests as well as a subjective rating of cognitive load (CL). The results showed that lexical annotations led to a better performance on the unannounced immediate meaning recall test. In the pop-up window condition, high capacity readers were able to supply more definitions for the target words than low capacity readers on the delayed post-test. While no effects of WM, gloss type, or gloss location emerged for the reported CL, pop-up window annotations were the most frequently accessed ones.
Keywords: annotations; cognitive load; electronic reading; glosses; incidental vocabulary learning; working memory; MULTIMEDIA ANNOTATIONS; COMPREHENSION; ACQUISITION; CONTEXT; LANGUAGE; LEARNERS; FORMS; FOCUS; Education & Educational Research; Linguistics